(untitled) (Research, Society and Development, 2020)
The number of flights and passenger frequencies has decreased significantly, which is an impact of the airline’s tariff policy which sets prices close to the upper limit for each class. Based on data from the Indonesian Central Bureau of Statistics (BPS) it was stated that the movement of passengers in January 2019 decreased by 6.7 million people or decreased by 16.07% compared to December 2018 and the Soekarno-Hatta Airport in Tangerang experienced the largest decline of 23.31 %. This condition will certainly threaten the company’s efforts to achieve its predetermined targets, namely one of the revenue targets of 11.4T and of course aero revenue as the biggest contributor becomes threatened and the assumption of non-aero income with a composition of 35% of revenue aero. Related to this, that in order to increase non-aero income there are opportunities that are very possible by developing support areas in the subsidiaries. Subsidiaries are very potential due to the flexibility of the portfolios owned by the subsidiaries and profits that can be directly consolidated into the group. This research to analyze current business of PT Angkasa Pura Solusi, by analyzing external and internal conditions in order to increase the portion of non-cash income in the corporate income structure. Then, it is expected to formulate appropriate strategy for PT Angkasa Pura Solusi based on Analysis in order to increase the portion of non-captive income in the APS revenue structure and the final step is to develop action plan from proposed corporate strategy in order to increase retail revenue by implementing business model strategies. In order to reach the goals from the aims, the author use business model canvas and marjeting mix to create the strategy. And to strengthen the quality of the strategy, the author started to analize the conditions using the TOWS Matrix. Finally, the conclusion is offered based on the analysis result.